The influence of social mobility perception and expectation on residents’ health: the role of subjective well-being and physical exercise - Liu, Xi; Zheng, Junyi; Kuang, Yan (Frontiers in Public Health, 2025)
BackgroundResidents’ Health is crucial for the effective implementation of the “Healthy China 2030” strategy and the sustainable development of society. However, there is still significant room for advancement in academic discussions on ensuring residents’ health.ObjectiveThis study aims to explore the relationship between social mobility perception and expectation and residents’ self-rated health, and further explore the mediating role of subjective well-being in this, the moderating role of physical exercise, and to provide reference for more targeted development and implementation of residents’ health policies.Materials and methodsBased on the data collected from 4,372 valid samples in the 2021 Chinese General Social Survey (CGSS), the Bootstrap method was used to test the mechanism of social mobility perception and expectation on residents’ self-rated health.ResultsBoth social mobility perception and expectation had significant positive effects on residents’ self-rated health. They indirectly contribute to residents’ self-rated health through the important mediating role of subjective well-being. In addition, physical exercise played an important moderating role in the relationship between social mobility perception and residents’ self-rated health. However, physical exercise did not have a significant moderating effect on the relationship between social mobility expectations and residents’ self-rated health.ConclusionThis study expands the understanding of the relationship between social mobility and residents’ health in China, providing practical insights for effective strategies to promote residents’ health.